Analysis of Excavation Methods Against Deformation in Highway Tunnels - Aryanti, Dian Eka; Saptono, Singgih (Newinera Publisher, 2024)
Cisumdawu tunnel is a highway tunnelling which composed of very weak rock mass conditions has an average compressive strength less than 1 MPa. It is located below groundwater level. The shape of tunnell is horseshoe, diameter of tunnel section 14,413 m and height 11,083 m. Cisumdawu tunnel is a shallow tunnel which has a maximum overburden of 52,8 m and minimum overburden approximately 14 m. In the case of shallow tunnel which has a large section could be lead an instability during tunnel construction. Tunnel deformation analysis is using an observation and numerical modelling approach with finite element method which is assisted by RS 2019 (Rocscience) software. Based on the research is obtained that excavation method greatly affects the level of deformation that occurs during tunnel construction. As tunnelling advanced, Vertical displacement in the longitudinal direction using three bench seven step excavation method is smaller than full face and bench excavtion method. The maximum displacement using three bench excavation method is -4.23 mm, the full face method is -5.51 mm and the bench method is -4.91 mm. The amount of displacement is affected by the length of excavation and stage in tunnelling. The rate of deformation is increasing as the length of excavation getting deeper, but this is applied in unsupported tunnel.